The Father of Filipino Austerity Central Bank Governor Miguel Cuaderno and Anti-inflationary Ideology in the 1950s - Claudio, Lisandro E. (Philippine Studies: Historical and Ethnographic Viewpoints, 2021)
Most economic analysts have argued that the failed currency policy of the Philippine Central Bank during the 1950s prevented the development of a robust export sector. Thisarticle examines the economic thinking that led to the Central Bank’s policies through a reassessment of the ideas of its first governor, Miguel Cuaderno. Reading Cuaderno’s memoirs and speeches from the period shows that anti-inflationary beliefs consistent with twentieth-century ideas of austerity informed his thinking. Thearticle hopes to contribute to the literature on “macroeconomic policy regimes” by examining how they are produced and reified through language.